Sibila - Arredondo, Teresa (Argentina, 2012)
One night, Teresa Orredondo’s family receives a phone call from Peru saying that their aunt Sibila was in prison accused of forming part of the Shining Path. Orredondo was seven years old, and her parent’s protective silence kept Sibila’s arrest shrouded in mystery for the 15 years of her prison sentence. Today she is free and Orredondo is attempting to hear hear story -- a journey that builds the present by looking at the past. It is an encounter between two generations looking for dialogue.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films